Наративна оптика поеми Тараса Шевченка “Катерина” - Ткачук, М. (Слово і Час, 2009)
У статті досліджується наративна стратегія зазначеної поеми. У художньому світі твору гетеродієгетичний
(третьоособовий) наратор розповідає про історію зведеної дівчини, виступає експліцитним, тобто явним
розповідачем, заявляючи про себе в ліричних відступах. Він дає оцінку вчинкам персонажів, моделює
центрогеройний сюжет, повчає уявних читачів і безпосередньо звертається до Катерини, співчуваючи їй. The article analyses the narrative strategy used in the poem “Kateryna” by Taras Shevchenko. It is argued
that a heterodiegetic narrator of the poem re-tells the story of the seduced and abandoned lass, therefore
acting as an explicit narrator which manifests himself in the numerous lyrical digressions. In this function, the
narrator comments upon the behaviour of the characters, shapes the character-centered plot, preaches to the
fictitious reader, and addresses himself directly to Kateryna, showing his sympathy to her. В статье исследуется нарративная стратегия поэмы
“Катерина” Тараса Шевченко. В художественном
мире произведения гетеродиегетический (от третьего
лица) нарратор рассказывает историю брошенной
девушки, представляется эксплицитным, то есть
явным повествователем, заявляя о себе в лирических
отступлениях. Он оценивает поступки персонажей, моделирует центрогеройный сюжет, напутствует
воображаемых читателей и непосредственно обращается к Катерине, сочувствуя ей.